2020
DOI: 10.1108/jes-11-2018-0388
|View full text |Cite
|
Sign up to set email alerts
|

US economic policy uncertainty spillover on the stock markets of the GCC countries

Abstract: PurposeThis study aims to investigate the nature and degree of US economic policy uncertainty spillover on the stock markets of a group of non-conventional economies like the Gulf Cooperation Council (GCC) countries, where a risk-sharing-based financial system is prominent and foreign investment, risk-free interest, derivatives, etc. are not as widespread as in the western economies.Design/methodology/approachthe monthly data of 1992–2018, linear and nonlinear structural vector autoregression (VAR) model, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Accordingly, the risk and uncertainty variables were positioned in first place in the ordering of the SVAR model. This ordering is consistent with those by Baker et al (2016), Caggiano et al (2017), Colombo (2013), Istiak (2021), and Istiak and Alam (2020), who placed the risk and uncertainty variables in first place in the ordering of the SVAR. Table 3 indicates that all the Granger variables cause tourism's contribution to GDP.…”
Section: Methodology and Datasupporting
confidence: 90%
“…Accordingly, the risk and uncertainty variables were positioned in first place in the ordering of the SVAR model. This ordering is consistent with those by Baker et al (2016), Caggiano et al (2017), Colombo (2013), Istiak (2021), and Istiak and Alam (2020), who placed the risk and uncertainty variables in first place in the ordering of the SVAR. Table 3 indicates that all the Granger variables cause tourism's contribution to GDP.…”
Section: Methodology and Datasupporting
confidence: 90%
“…The study further suggests that policy uncertainty leads to delayed economic recovery, particularly after the recession, as households defer their consumption decisions. Istiak and Alam (2020) examined the impact of US economic policy uncertainty on the stock market fluctuations for Gulf Cooperation Council (GCC) countries. Based on monthly observations from 1992 to 2018 using the linear and nonlinear structural vector autoregression models, the study found that an increase in US economic policy uncertainty leads to a significant decline in the stock market index of GCC countries.…”
Section: Policy Uncertainty Impact On Consumer Confidence and Busines...mentioning
confidence: 99%
“…The literature exploring the connection of return and/or volatility of the stock market with EPU has flourished across the globe, including both developed and emerging economies. Extensive research has mainly concentrated on exploring the relationship of own country EPU with the returns/volatility of local stock markets (Bekiros et al, 2016;Rahman et al, 2019) among others, while various studies explored the transnational influences of EPU on the stock markets of other emerging economies such as Brazil, Australia, Canada, Japan, China, South Africa, and on the financial markets of some trade group countries such as ASEAN, BRIC, EU and GCC (Balcilar et al, 2019;Carri ere-Swallow & C espedes, 2013;Istiak & Alam, 2019;Kang & Ratti, 2015) among others.…”
Section: Relevant Researchmentioning
confidence: 99%